19 A tale of ill-managed pain and the opioid epidemic. Issue Volume 24:Issue Supplement 1(2019) (July 2019) - Mikhaeil, John; Huang, Alexander; Clarke, Hance; Wasowicz, Marcin
Abstract : The use of opioids to treat chronic non-cancer pain has increased dramatically in the last decade. Simultaneously, this surge in prescribing practices has been correlated to an almost four-fold increase in opioid-related deaths. Despite recent efforts to control the distribution of opioids and the introduction of abuse-deterrent opioid formulations, the epidemic is still yet to be fully targeted with a multi-factorial approach. In order to better understand how this crisis exists, it is important to examine patterns beginning in the 1980s. At that time, pharmaceutical companies marketed the use of opioids to treat pain and assured clinicians that the addiction profile was low, but these claims were not based on evidence-based medicine. Within a few years, the same companies promoted these drugs for use in long-term non-cancer pain, despite the lack of good evidence. Regardless, this 'mentality' was adapted by clinicians based on the pharmaceutical companies' misrepresentation, which sparked the first of three major waves of increased opioid prescribing. The number of opioid prescriptions increased among primary care clinics and hospitals, and an increased amount of opioid diversion took place. Pharmaceutical companies responded to the public outcry by developing abuse-deterrent formulations such as an extended release oxycodone (OxyContin). These prescribing practices led to increased rates of opioid over-sedation and opioid-related deaths. The second wave began around 2010, as efforts were made to decrease opioid prescribing, leading to the increased popularity of a cheap, widely available option – heroin. Finally, the last resurgence was seen in 2013 due to newer synthetic opioids such as fentanyl. When a patient undergoes a surgical procedure, some level of pain is anticipated post-operatively, and the level of severity and duration varies patient-to-patient. Indirectly related to the illicit opioid epidemic, opioid-prescribing in the postoperative period has increased dramatically, feeding yet another epidemic. Although opioids are often prescribed to address the need for pain management, this is often done without a long-term plan to eventually wean off these medications. As a result, patients are ultimately left with inappropriately managed chronic pain and almost half of these patients continue to use opioids as more of a 'band-aid' solution. The issue becomes more complex as these patients seek care from their primary care physicians who may not have experience in weaning patients off opioids. Although some success has been seen with the implementation of prescribing guidelines and educational interventions, new programs need to be implemented to address this systemic issue. This led to the concept of a Transitional Pain Service with a focus on high-risk patients with complex pain management and opioid weaning. This is managed through an interdisciplinary team which is led by anesthesiologists with the goal of minimizing the risk of developing chronic pain postoperatively and long-term opioid use. Through the Transitional Pain Service, patient's pain management needs are being addressed through a multidisciplinary model and programs are being implemented to combat the growing opioid epidemic that stemmed from a lack of evidence-based medicine.